Assessment and documentation of women's labour pain: A cross-sectional study in Swedish delivery wards. Issue 2 (June 2015) - Bergh, Ingrid H.E.; Johansson, Anna; Bratt, Annelie; Ekström, Anette; Mårtensson, Lena B.
Abstract Background A woman's pain during labour plays a dominant role in childbirth. The midwife's role is to assess the degree of pain experienced during labour. When professionals respond to labour pain with acknowledgement and understanding, the woman's sense of control and empowerment is increased, which could contribute to a positive experience of childbirth. The aim of this study is to describe how labour pain in Swedish delivery wards is assessed and documented. Methods This quantitative descriptive study was designed as a national survey performed through telephone interviews with the representatives of 34 delivery wards in Sweden. Results and conclusion The majority of the participating delivery wards assessed and documented women's labour pain, but in an unstructured manner. The wards differed in how the assessments and documentation were performed. In addition, almost all the delivery wards that participated in the survey lacked guidelines for the assessment and documentation of the degree of pain during labour. The findings also showed that the issue of labour pain was sometimes discussed in the delivery wards, but not in a structured or consistent way.